Analisis Standarisasi Laboratorium Fisika Di SMA Negeri Kalisat - Reza, Moch Dimas; Lathifah, Harirotul; Fahmiah, Nabila; Sari, Puput Aprilia Eka; Anggraeni, Diva Kanaya; Nuraini, Lailatul; Harijanto, Alex (Jurnal Ilmiah Wahana Pendidikan, 2024)
The research was conducted in order to find out related to the standardization of physics laboratories in SMA Negeri Kalisat Jember to fulfill the final project of the laboratory management course. This research is included in descriptive research using a qualitative approach. The research was conducted on September 22, 2023 at SMA Negeri Kalisat Jember. The subject of our research is the person in charge of the laboratory, laboratory room and laboratory warehouse at SMA Negeri Kalisat Jember. From direct observation there is a laboratory organizational structure, SOP and laboratory rules. Techniques used in this research with data collection using research instruments, namely observation sheets, interview guidelines and documentation. The results of this standardization research are supported by physics laboratory infrastructure in the school with an average of 100% including a very good classification, the standardization of the carrying capacity of the facilities has an average percentage of 100% with a very good classification, the standardization of laboratory personnel has an average percentage of 95% in the very good category, Overall the physics laboratory of SMA Negeri Kalisat Jember has a very good category standardization with an average of 96.6%.